New Straits Times, 17 December 2007 (The New Straits Times Press (M) Bhd, 2007)
The Meteorological Department has lifted the red alert status for Pahang and orange alert status for Kelantan and Terengganu, but warned of heavy rains and thuderstorms with strong winds over Penang and southern Kedah.